Анализ релаксации контактного давления между вязкоупругим композитным бандажом и трубопроводом - Сукиасов, Владимир Георгиевич (НТУ "ХПИ", 2016)
Изложены постановка и методика приближенного аналитического решения задачи о взаимодействии композитного ремонтного бандажа со стальным трубопроводом. Вязкоупругие свойства ортотропного композита моделируются на основе принципа соответствия Вольтерра, в сочетании с правилом смесей. Зависимость контактного давления от времени получена с помощью одностороннего интегрального преобразования Лапласа для различных значений объемного содержания армирующих волокон.

The statement and an approximate analytical method of solving the problem of interaction between the composite repair band and a steel pipeline are outlined. Computational model is a two-layer cylinder in plane strain conditions, under internal pressure. With one-sided Laplace transformation the viscoelastic problem solution is obtained in the images, according to the Volterra correspondence principle. The viscoelastic properties of the orthotropic composite are simulated by mixtures rule, taking into account the characteristics of reinforcing fibers and a polymer matrix. To find the original describing the time dependency of the contact pressure used the approximation of the transcendental part of image by truncated power series. The calculations were performed for different values of the reinforcing fibers volume content.
Analysis the relaxation of contact pressure between viscoelastic composite band and pipeline
Keywords: бандаж; трубопровод; свойства вязкоупругие; композит; давление контактное; преобразование Лапласа; band; pipeline; viscoelastic properties; composite; contact pressure; Laplace transformation